2023
DOI: 10.32360/acmar.v55i2.62544
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Shark Meat Traded as Cação in Southwestern State of São Paulo, Brazil

Abstract: The meat of sharks and rays is commonly traded in Brazil under the generic name of cação. This compromises the monitoring of which species are being traded. In the present study, molecular marker techniques were applied to the species-level identification of elasmobranch meat traded in the southwest of the State of São Paulo. A total of 15 meats purchased in 2019 were partially sequenced (up to 655 base pairs) for the mitochondrial cytochrome c oxidase subunit I (COI) gene. Of these meats, 14 were from Blue Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…It is possible that a reduction in monitoring and enforcement during the COVID-19 lockdown might also have increased the trade of endangered shark species, potentially explaining the sale of threatened and prohibited species identified here. However, comparison to the results of Merten Cruz et al [23] and Queiroz et al [36] gathered before the lockdown did not show a significant difference in the species traded.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…It is possible that a reduction in monitoring and enforcement during the COVID-19 lockdown might also have increased the trade of endangered shark species, potentially explaining the sale of threatened and prohibited species identified here. However, comparison to the results of Merten Cruz et al [23] and Queiroz et al [36] gathered before the lockdown did not show a significant difference in the species traded.…”
Section: Discussionmentioning
confidence: 54%
“…Blue shark was by far the most prevalent species identified in products (80%) included in this study. Other Brazilian studies have also identified P. glauca as the most commonly sold species, accounting for between 24% [12] and 93% [36] of products. The result is consistent with the fact that blue shark represents 49-90% of the total pelagic sharks captured by commercial longline fisheries [9,38], making this species the most common and widely traded shark in Brazil and internationally [24,39].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations